The Role of Digital Media in Overcoming the Learning Saturation of Islamic Religious Education and Ethics in Elementary Schools - Hanum, Fajar Lutfia; Zakiyah, Zakiyah (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2026)
Learning boredom at the elementary school level is often triggered by the dominance of monotonous lecture methods and non-contextual memorization materials, thus hindering the effectiveness of Islamic Religious Education and Ethics Education (PAIBP) learning. This study aims to describe the implementation of digital media, identify forms of learning saturation, and analyze the role of digital media in overcoming this phenomenon in SD N Karangdawa 02. Using a descriptive qualitative approach, this study involved school principals, PAIBP teachers, students in grades IV and VI, and parents as participants. Data were collected through in-depth interviews, participant observations, and documentation studies, which were then validated using triangulation of sources and techniques. The results of the study show that the use of digital media in the form of animated videos and gamification integrated with active learning methods has been proven to be able to significantly reduce student learning saturation. Digital media plays a role in increasing motivation, visualizing abstract concepts, and transforming the classroom atmosphere into a more dynamic one. These findings confirm that successful technology integration requires synergy between teachers' pedagogical competence, school infrastructure support, and active parental involvement to create an innovative learning ecosystem for the digital native generation.